2018
DOI: 10.5937/ratpov55-15198
|View full text |Cite
|
Sign up to set email alerts
|

Field performance of abnormal maize seedlings

Abstract: The aim of this study was to investigate field emergence parameters, number of plants that reached reproductive stage and yield of seed lots with different count of abnormal seedlings. In standard germination test these seedlings are discarded from the count of germinated seed, presuming that they will not develop into normal plants. Five lots of hybrid NS 640 with different percentage of abnormal seedlings were tested. Results showed that in favourable environment conditions, large number of abnormal seedling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…After 14 days plumule failed to develop and root formed a loop. According to Vujosevic [20] abnormal seedlings are less likely to develop into normal plants. Lower germination and higher abnormality of seedling indicated that deterioration of seeds in Bambara groundnut most likely begin to occur on 2 years period of storage.…”
Section: Final Germination Percentagementioning
confidence: 99%
“…After 14 days plumule failed to develop and root formed a loop. According to Vujosevic [20] abnormal seedlings are less likely to develop into normal plants. Lower germination and higher abnormality of seedling indicated that deterioration of seeds in Bambara groundnut most likely begin to occur on 2 years period of storage.…”
Section: Final Germination Percentagementioning
confidence: 99%
“…From the aspect of differences in the seed accelerated ageing test between organically and conventionally produced seeds, a statistical significance was determined for off-type seedlings (almost three-fold higher percentage in the conventionally produced seeds -15.00%) and non-germinated seeds (three-fold higher percentage in the conventionally produced seeds -38.75%). Vujošević et al (2018) tested five seed lots of the maize hybrid NS 640 with different proportions of off-type seedlings to observe parameters of the germination rate, number of plants in the reproductive phase and yields. The percentage of off-type seedlings amounted to 1%, 3%, 38%, 57% and 64% in Lot5, Lot4, Lot3, Lot2 and Lot1, respectively.…”
Section: ____________________________________________________________mentioning
confidence: 99%
“…The percentage of off-type seedlings in organically produced seeds determined in our study (5.75%; 5.50%) was the closest to the Lot4 with 3% of off-type seedlings. Results gained by Vujošević et al (2018) showed that, under favourable conditions, a large number of off-type seedlings emerged, reached the reproductive phase and participated in the formation of yields, while the emergence of seeds from lots with a high number of offtype seedlings was delayed. According to Milivojević (2016), in the first evaluation, four days after germination, the percentage of normal seedlings amounted to 79.67% and 31.87% for the seeds produced in 2014 and 2011, respectively.…”
Section: ____________________________________________________________mentioning
confidence: 99%
“…Kadar air benih dihitung menggunakan rumus (ISTA, 2018): (Vujosevic et al, 2018). Penentuan periode perkecambahan V. venulosa pada hitungan awal dan akhir perkecambahan mengadopsi metode yang telah dihasilkan Sadjad (1994), bahwa pola yang terbentuk pada kurva dilakukan analisis secara visual untuk menentukan perhitungan awal dan akhir.…”
Section: Kadar Air (Ka)unclassified